2010
DOI: 10.1183/09031936.00194209
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and plasma levels of inflammatory biomarkers in COPD

Abstract: Previous studies suggest a relationship between systemic inflammation and body composition in chronic obstructive pulmonary disease (COPD). We examined the relationships between body composition (fat free mass index (FFMI) kg?m -2 and fat mass index (FMI) kg?m -2 ) and three plasma inflammatory markers C-reactive Protein (CRP), soluble tumour necrosis factor receptor 1 (sTNF-R1) and osteoprotegerin (OPG) CRP and sTNF-R1 levels correlated positively with both FFMI and FMI. The adjusted regression coefficients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 40 publications
(72 reference statements)
4
15
1
4
Order By: Relevance
“…However, one study found decreasing levels of sTNFαR1 with lower FEV 1 values in multiple regression analysis [20]. These data could not be confirmed in the present study.…”
Section: Disease-related Factorscontrasting
confidence: 99%
See 2 more Smart Citations
“…However, one study found decreasing levels of sTNFαR1 with lower FEV 1 values in multiple regression analysis [20]. These data could not be confirmed in the present study.…”
Section: Disease-related Factorscontrasting
confidence: 99%
“…In line, Takabatake and colleagues reported an association between both sTNFα receptors and the percentage of fat mass in COPD [24]. A recent manuscript concluded that both circulating CRP and sTNFαR1 were positively associated with fat mass rather than fat free mass [20], data which are confirmed in the present study.…”
Section: Host-related Factorssupporting
confidence: 90%
See 1 more Smart Citation
“…Second, both COPD and IBD are considered to be driven by low-grade chronic systemic inflammation so that circulating lymphocyte activity may be a contributory factor [45][46][47]. During inflammation, bronchial lymphoid tissue is regulated by lymphocyte traffic from the lung tissue through the general circulation [48].…”
Section: Respiratory Tractmentioning
confidence: 99%
“…T.M.L.Eagan et al [46] получили обратные результаты: выявлена взаимо связь FMI и FFMI и уровня СРБ и sTNF R1. В проти воположность показателям СРБ и sTNF R1, низкий FMI ассоциировался с высоким остеопротегирином (OPG), хотя связь между FFMI и OPG не была най дена.…”
Section: кровьunclassified